RESPON PENAMBAHAN EFFECTIFE MICROORGANISM-4 (EM-4) TERHADAP KUALITAS NUTRISI FERMENTASI LIMBAH BAGASSE TEBU UNTUK PAKAN TERNAK - Fariani, A.; Akhadiarto, Sindu (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
The objective of this research was to obtain the best dosage of using EM-4 in sugarcane waste. This research was done in two processes. First process was fermentation ofsugar cane waste within 9 days in Ã¢â‚¬Å“Nutrisi dan Makanan TernakÃ¢â‚¬Â Laboratory at SriwijayaUniversity. Second process was analyzed the nutritive value of sugar cane waste, inLaboratory of ruminant and chemical feed at Faculty of Animal Husbandry, PadjajaranUniversity, Bandung.A Complete Randomized Design with four treatments and three replications was carriedout. The experimental diets were : E0 (control), E1 (waste of sugar cane + 7,5ml EM-4),E2 (waste of sugar cane + 15ml EM-4), E3 (waste of sugar cane + 22,5ml EM-4).Each treatment was added with rice straw 20% of dried weight sugar cane waste. Theparameters measured were dry matter, crude fiber, crude protein, NFE and crude fat.The results of this research showed that the treatment improved significantly to drymatter, crude fiber, crude protein, NFE and crude fat. The conclusi-on of the researchwas treatment by addition EM-4 15ml give the best result in all treatments.